Effects of a core stabilization training program on balance ability in persons with Parkinson's disease: a randomized controlled trial - Cabrera-Martos, Irene; Jiménez-Martín, Ana Teresa; López-López, Laura; Rodríguez-Torres, Janet; Ortiz-Rubio, Araceli; Valenza, Marie Carmen (Clinical rehabilitation, 2020)
To explore the effects of an eight-week core stability program on balance ability in persons with Parkinson's disease. Randomized controlled trial. A local Parkinson's association. A total of 44 participants with a clinical diagnosis of Parkinson's disease were randomly assigned to an experimental ( = 22) or control group ( = 22). The experimental group received 24 sessions of core training, while the control group received an intervention including active joint mobilization, muscle stretching, and motor coordination exercises. The primary outcome measure was dynamic balance evaluated using the Mini-Balance Evaluation Systems Test. Secondary outcomes included the balance confidence assessed with the Activities-specific Balance Confidence Scale and standing balance assessed by the maximal excursion of center of pressure during the Modified Clinical Test of Sensory Interaction on Balance and the Limits of Stability test. After treatment, a significant between-group improvement in dynamic balance was observed in the experimental group compared to the control group (change, 2.75 ± 1.80 vs 0.38 ± 2.15, = 0.002). The experimental group also showed a significant improvement in confidence (change, 16.48 ± 16.21 vs 3.05 ± 13.53, = 0.047) and maximal excursion of center of pressure in forward (change, 0.86 ± 1.89 cm vs 0.17 ± 0.26 cm, = 0.048), left (change, 0.88 ± 2.63 cm vs 0.07 ± 0.48 cm, = 0.010), and right (change, 1.63 ± 2.82 cm vs 0.05 ± 0.17 cm, = 0.046) directions of limits of stability compared to the control group. A program based on core stability in comparison with non-specific exercise benefits dynamic balance and confidence and increases center of mass excursion in patients with Parkinson's disease.